2023
DOI: 10.2459/jcm.0000000000001461
|View full text |Cite
|
Sign up to set email alerts
|

The gray areas of oral anticoagulation for prevention of thromboembolic events in atrial fibrillation patients

Abstract: Thromboembolic events (TEE) associated with atrial fibrillation (AF) are highly recurrent and usually severe, causing permanent disability or, even, death. Previous data consistently showed significantly lower TEE in anticoagulated patients. While warfarin, a vitamin K antagonist, is still used worldwide, direct-acting oral anticoagulants (DOACs) have shown noninferiority to warfarin in the prevention of TEE, and represent, to date, the preferred treatment. DOACs present favorable pharmacokinetic, safety and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…The CHA 2 DS 2 VASc risk score [2] confers two points for individuals aged more than 75 years, or one point when the age range is 65-74; therefore, young women (CHA 2 DS 2 VASc risk score = 1), or men (CHA 2 DS 2 VASc risk score = 0) without other risk factors are considered at minimal risk for stroke and should not be treated with oral anticoagulation (OAC) since these drugs, in this particular scenario, likely outweigh the risk of bleeding. On the other hand, AF studies addressing the risks of OAC and thrombosis account for only a small percentage of subjects with the above-mentioned features; even when a sole risk factor is added, yet benefits of OAC are unclear, thus opening a field of investigation requiring randomized clinical trials to fill the evidence gap in such heterogeneous population [99].…”
Section: Anticoagulation In Low Thromboembolic Riskmentioning
confidence: 99%
“…The CHA 2 DS 2 VASc risk score [2] confers two points for individuals aged more than 75 years, or one point when the age range is 65-74; therefore, young women (CHA 2 DS 2 VASc risk score = 1), or men (CHA 2 DS 2 VASc risk score = 0) without other risk factors are considered at minimal risk for stroke and should not be treated with oral anticoagulation (OAC) since these drugs, in this particular scenario, likely outweigh the risk of bleeding. On the other hand, AF studies addressing the risks of OAC and thrombosis account for only a small percentage of subjects with the above-mentioned features; even when a sole risk factor is added, yet benefits of OAC are unclear, thus opening a field of investigation requiring randomized clinical trials to fill the evidence gap in such heterogeneous population [99].…”
Section: Anticoagulation In Low Thromboembolic Riskmentioning
confidence: 99%
“…Improved materials and technology evolution in high volume and experienced hospital centres allow to perform transeptal puncture by simply adopting X-ray anatomical points in real time; on the other side, the actual exclusion of periprocedural LAA thrombus is a critical caveat that has prompted several trials in suggesting ablation under no interruption or minimally interruption of the DOACs [1,2,10]. Unfortunately, periprocedural TEE with or without uninterrupted DOACs does not warrant stroke-free procedures in all cases; perhaps, the atrial cardiomyopathy that develops when AF is not treated adequately, is responsible for loss of atrial contraction and transport function [12] that can be translated in increased risk of stroke in few cases, while others might experience cognitive decline and dementia [13,14]. However, what comes from the sub-analysis of the LATTEE registry is that a thorough evaluation of the AF clinical cases before TCA contributes to stroke risk abatement, mostly when oral anticoagulation is ongoing and CHA2DS2VASc score is low [3,8,11,15].…”
mentioning
confidence: 99%
“…Although many studies have clearly indicated that advantages of DOAC to prevent thrombotic events in specific clinical settings, some grey areas still exist when DOAC is compared to VKA [ 9 ]. This is the case of intracardiac thrombosis.…”
mentioning
confidence: 99%